From the Compact City to the X-Minute neighborhood: A Systematic Review of the Health and Wellbeing Impacts of Sustainable Urban Development Models (SUDMs) on Women. - Stevenson, Amy; Ponce Hardy, Vicki; Bailey, Nick; Toney, Jaime; Olsen, Jonathan R.; Meier, Petra (Journal of Urban Health, 2025)
Throughout the past 50 years, sustainable urban development models (SUDMs) have been introduced in cities across the world with the intention of limiting environmental air pollution and, more recently, greenhouse gas emissions. However, the health and wellbeing impacts that these interventions have had on different demographic groups are not well understood. Feminist urbanists have often critiqued hierarchical and non-participatory approaches to urban design for the detrimental impact they may have on women and minority groups. With x-minute neighborhood policies gaining popularity in urban planning across the world, gathering evidence on the potential gendered health and wellbeing inequalities impacts of these policies is a salient issue. Our research questions were as follows: (1) In the existing literature, what is known about the health and wellbeing impacts of SUDMs on women? (2) What mechanistic pathways are outlined in existing literature from SUDMs to gendered health outcomes? This review searched Medline, SCOPUS, Science Citation Index Expanded, Social Sciences Citation Index, and ASSIA. A broad range of outcomes was included in the search, from physical and mental health and wellbeing to health behaviors. We searched for empirical papers published in English before January 1st, 2024, without limiting the search by year or country of publication. Screening was performed on Rayyan with 15% of records double-screened. Critical appraisal was conducted using the AXIS tool for cross-sectional studies and CASP cohort checklist for longitudinal studies. Narrative synthesis was used to explore results in depth, with an effect-direction plot used to visually summarize findings. The initial search returned 1263 records. After duplicates were removed, 1194 records remained for screening. Of these, 301 were included for full-text screening, with 25 included for data extraction. Most of the included papers explored associations between SUDMs and women's physical activity. These relationships were typically positive, although some found no significant associations. Papers which explored the gendered mechanisms leading to outcomes tended to posit that having more convenient non-motorized access to a range of destinations on foot helped women to balance their paid and unpaid labor, leading to increased physical activity. Increased safety and reduced social isolation within SUDMs were also hypothesized as key contributing factors to women's increased physical activity. We found that there are research gaps in relation to mental health and long-term physical health outcomes.